Quociente respiratório: inovação tecnológica para o armazenamento de maçãs em atmosfera controlada dinâmica - Weber, Anderson (2013)
The conventional controlled atmosphere storage resulted in a significant improvement in the apples quality maintenance during the last decades, however, in this storage system further losses occur. Therefore, recently a new technique for storing apples was developed, called dynamic controlled atmosphere (DCA) which is monitored by chlorophylls fluorescence emission. This system is used commercially and is known as HarvestWatchTM (HW DCA). The aim of this study was to evaluate apple fruit quality with the use of the new DCA storage method with the respiratory quotient (RQ) monitoring and compare this new system with the HW ACD and the conventional controlled atmosphere (CA). Furthermore, the effect of the combination of 1-methylcyclppropene (1-MCP) application or higher temperature with the RQ DCA were evaluate. For that, experiments were divided in four scientific articles in this thesis. Initially, different levels of the respiratory quotient were tested to control the DCA for maintain the apple quality after storage. Thereafter, the effect of the combination of 1-MCP application and elevated storage temperature for ‘Royal Gala’ and ‘Fuji Suprema’ apples, produced in Brazil, and ‘Braeburn’ apples, produced in Germany was tested. The new RQ DCA was always compared with the HW DCA and the conventional CA. The storage time and temperature were 7 to 9 months and 0.5, 1 or 1.5°C for ‘Royal Gala’ apples, 9 months and -0.5°C for ‘Fuji Suprema’, and 8 months and 1 or 3°C for ‘Braeburn’ apples, respectively. After storage, the apples were also exposed in shelf life for 7 days at 20°C. The DCA with RQ higher than 2 results in tissue damage and alcoholic taste of apples flesh, therefore, not suitable for DCA monitoring. The RQ most suitable for storage of ‘Royal Gala’ and ‘Fuji Suprema’ apples were 1.5 to 2, and for ‘Braeburn’ apples, 1.5. With these respiratory quotients, for controlling oxygen partial pressures in the DCA, the apples after storage had a lower incidence of physiological disorders and higher flesh firmness, mainly due to the reduced synthesis of ethylene and respiratory rate. The reduction in the metabolic activity is due to the ethanol production in the apples flesh under the hypoxic conditions, which leads in the inhibition of ethylene biosynthesis way and, therefore, reducing the maturation process. For ‘Royal Gala’ and ‘Fuji Suprema’ apples, the association of 1-MCP application with the RQ DCA results in lower respiratory and fermentation rate and, therefore, maintained the highest total soluble solids and titratable acids content, however, the 1-MCP application had no effect on flesh firmness in ‘Royal Gala’ apples. The incidence of physiological disorders was the same or lower if the ‘Royal Gala’ apples, produced in Brazil, was stored at 1.5°C and the ‘Braeburn’ apples, produced in Germany, was stored at 3°C than if they were stored at 1°C. Therefore, higher temperatures maintain the same apple quality during and after storage and, in addition, energy can be saved due to the lesser cold generation necessity